RESPON TANAMAN KENTANG (Solanum tuberosum L.) PADA BERBAGAI KETEBALAN MEDIA COCOPEAT DAN WAKTU PEMBERIAN NUTRISI SUNDSTROM - FAJRIN PRAMANA PUTRA; SAPARSO SAPARSO; SLAMET ROHADI; RONI ISMOYOJATI (Universitas Lancang Kuning, 2019)
ABSTRACT This research purposes know the growth and tubers yield of potato (G0) under various thickness of cocopeat media and time of sundstrom nutrient giving. The research was carried in the screen house in Pandansari, Paguyangan district from October 2014 until January 2015. The research used Randomized Complete Block Design with 2 factor and 3 repetitions. The first factor was the thickness of media with three levels; 10 cm, 15 cm, and 20 cm. The second factor was the time of nutrient solution giving with two levels; once for three days and once for six days. The results of the research showed that the thickness of cocopeat media 20 cm was good for plant height, total of leaves, wide of plant leaves, and improve the roots length 23.6 %. Time of nutrient giving once for three days was good for plant height, total of leaves, wide of plant leaves, weight of fresh plant, weight of dry plant and the result was good for stolon effectiveness (49.84%), weight of fresh tuber (137.85 g), and weight of dry tuber (21.55 g). The treatment of cocopeat medium thickness and time of nutrient giving had not been able to provide increased yield of potato tuber (G0).